The Italian Diaspora in South Africa Nostalgia, Identity, and Belonging in the Second and Third Generations - Marchetti-Mercer, Maria Chiara (Routledge Studies in Development, Mobilities and Migration, 2023)
This book investigates the experiences of second- and third-generation Italians living in South Africa, exploring how nostalgia for Italy influences their sense of identity and belonging. The Italian community in South Africa is a unique diaspora, with a complex history, including roots in Italian colonial activities in Africa, and in World War II. This book looks at how the descendants of these early migrants take pride in being Italian and value the Italian language. They also ascribe much importance to their family roots, and have often created a romanticized image of Italy, mostly based on childhood vacation visits. The longing for an imaginary idealized version of Italy is closely linked to their wider search for a sense of identity and belonging against the backdrop of South African society, currently still grappling with its own multicultural identity. Interdisciplinary by design, this book draws on insights from both cultural studies and psychology in order to shine a light on an important and under-studied diasporic community. The book will be of interest to scholars from across migration studies and the Humanities in general. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license.